A comparison of two different defensive based playing formations on the running activity profiles of soccer teams - Cetin, O.; Isik, O.; Beyleroglu, M.; Tokul, E.; Hazar, M. (Kinesiologia Slovenica, 2021)
This study aimed to examine the effects of two different defensive based playing formations (3- Defender formation and 4-Defender formation) on both the reference and the opponent teams' running activity profiles. 8 official matches (n=4, 3-Defender formation; n=4, 4-Defender formation) of Galatasaray football team (Turkish Super League) and opposition teams performed with two different playing formations were monitored. The sample matches were monitored and analyzed using a multiple-camera computerized tracking system. Running activity data variables obtained from the software were analyzed in 5 different categories (total running distance in kilometers, mean speed in km.h-1, high-intensity running (20 km.h-1 to 24 km.h- 1) distance in meters, sprint (>24 km.h-1) distance, sprint numbers. The results of this study indicate that running activity profiles of reference and opposition teams generally do not differ (p >0.05) according to the different game formation of the reference team. Only the reference team's total running distance was higher (p <0.05) in the 4-Defender formation than the 3-Defender formation (2.52%)